2020
DOI: 10.3390/ani10081380
|View full text |Cite
|
Sign up to set email alerts
|

Novel Encapsulated Calcium Butyrate Supplement Enhances On-Farm Dairy Calf Growth Performance and Body Conformation in a Pasture-Based Dairy Production System

Abstract: The effect of supplementing neonatal heifer calves with varying levels of ECAB on pre-weaning growth performance was investigated. Post-weaning growth was also measured, to determine any carry-over effect of pre-weaning supplementation of ECAB. Forty-eight heifer calves (7 ± 0.4 days old, average liveweight of 39.3 ± 5.3 kg) were utilized in a complete randomised experimental design, comprising 16 calves per pen, randomly allocated to one of the following three treatments: (1) Basal commercial calf starter mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…This increased antioxidant capacity can translate into enhanced ADG, dry matter intake, and feed efficiency. Improving the digestibility of pre-weaning calves through nutrient absorption by enhancing the development of rumen papillae has been investigated by Malau-Aduli et al., (2020) and Diao, Zhang and Fu, (2019) . Strategies to improve rumen papillae development include but are not limited to, increasing available volatile fatty acids such as butyrate, altering the particle size of the diet and supplementation with probiotics ( Malau-Aduli et al., 2020 ; Diao, Zhang and Fu, 2019 ; McCurdy et al., 2019 ).…”
Section: Maternal Nutrition Foetal Development and Bullsmentioning
confidence: 99%
See 2 more Smart Citations
“…This increased antioxidant capacity can translate into enhanced ADG, dry matter intake, and feed efficiency. Improving the digestibility of pre-weaning calves through nutrient absorption by enhancing the development of rumen papillae has been investigated by Malau-Aduli et al., (2020) and Diao, Zhang and Fu, (2019) . Strategies to improve rumen papillae development include but are not limited to, increasing available volatile fatty acids such as butyrate, altering the particle size of the diet and supplementation with probiotics ( Malau-Aduli et al., 2020 ; Diao, Zhang and Fu, 2019 ; McCurdy et al., 2019 ).…”
Section: Maternal Nutrition Foetal Development and Bullsmentioning
confidence: 99%
“…Recent research into the effects of supplementing encapsulated calcium butyrate to pre-weaning calves ( Malau-Aduli et al., 2020 ; McCurdy et al., 2019 ) evaluated ADG, chest girth, wither height, body length and body condition score and found that supplemented calves weighed on average, nine kilograms more and had an ADG that was 0.1 kg higher than the unsupplemented group ( Malau-Aduli et al., 2020 ). The bodyweight (BW) of calves is moderately influenced by maternal genetic predisposition of the dam because the maternal heritability of BW is 0.42 in beef cattle ( Cortés-Lacruz et al., 2017 ).…”
Section: Maternal Nutrition Foetal Development and Bullsmentioning
confidence: 99%
See 1 more Smart Citation